ASSESSMENT OF AQUATIC PHYSIO-CHEMICAL PARAMETERS OF SHIVNATH RIVER FROM DAGAURI VILLAGE ZONE BILASPUR CHHATTISGARH - K.C. Gendle, M. R. Augur, P.K. Singh (Chelonian Research Foundation, 2024)
Water is a valuable essential and survive vital composition of universal Nature Biotic and abiotic life cycles . Surface river water has one Important for living society besides its habitats. However, there are various micro-organism ions and suspended particles, mineral dissolved components. According to the selected site of River water sample are main source of multiple purpose required for the daily human needs and all other activities. Shivnath river water is one of the major sources for domestic uses may part of dagauri village area. The present investigation deals with the study of chemical parameters , studies have in this river on different sites by a specially prepared. Aquatic assessment questionnaire chemicals & inorganic meters. Water quality Index and various physio-chemical Analysis of river drinking water of Different 8 sites of Dagauri village zone Bilaspur had studied in Over a period of three months (Oct.-Dec. 2022) reading had observed to analyse different physio-chemical parameters Turbidity, Total Hardness (Mg &Ca), COD & BOD, pH the results were found in the range of 2.51–3.8 NTU, 300-650 mg/l , 15.3-18.5 mg/l ,1.3-3.2 mg/l & 7.0-8.1 pH value. Respectively while F, Cl, No3, So4 were in the range of 0.56-2.5 mg/l. 250-400 mg/l, 6-28 mg/l, and 12-40 mg/l . Iron and zinc heavy metal were present in range of 0.48-1.12 ml/l, 1.26-1.29 mg/l. The present study has it’s almost importance for hygienic point of view in the Public Interest and its consequence with respect to health hazard. Bilaspur district Dagauri village zone was selected for the purpose of Investigation many illiterate villagers and use of surface river water for their drinking purpose & domestic activity. Keyword- Public health, Aquatic environment, Physio-chemical, Investigation